2022
DOI: 10.1177/00220345211062475
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Oral Health-Related Birth Cohort Studies: Toward a Global Consortium

Abstract: The multidisciplinary nature and long duration of birth cohort studies allow investigation of the relationship between general and oral health and indicate the most appropriate stages in life to intervene. To date, the worldwide distribution of oral health-related birth cohort studies (OHRBCSs) has not been mapped, and a synthesis of information on methodological characteristics and outcomes is not available. We mapped published literature on OHRBCSs, describing their oral health-related data and methodologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…In general, our data show a continuous caries incidence over the whole observation period. There are not many long-term studies of oral health, for example cohort studies [ 33 ], and most cover periods from birth to adolescence but not to later ages. Those with longer follow-up periods beyond the age of twenty have either looked at specific ethnicities (Australia ABS), do not report long-term data for dental caries (Avon Longitudinal Study of Parents and Children (ALSPAC), Iowa Facial Growth Study, Northern Finland Birth Cohort (NFBC), Pelotas Birth Cohort Study (2004)) or report no or only self-reported caries data (British Cohort Study, National Child Development Study (NCDS), Newcastle Thousand Families Cohort Study, Pelotas Birth Cohort Study (1993)).…”
Section: Discussionmentioning
confidence: 99%
“…In general, our data show a continuous caries incidence over the whole observation period. There are not many long-term studies of oral health, for example cohort studies [ 33 ], and most cover periods from birth to adolescence but not to later ages. Those with longer follow-up periods beyond the age of twenty have either looked at specific ethnicities (Australia ABS), do not report long-term data for dental caries (Avon Longitudinal Study of Parents and Children (ALSPAC), Iowa Facial Growth Study, Northern Finland Birth Cohort (NFBC), Pelotas Birth Cohort Study (2004)) or report no or only self-reported caries data (British Cohort Study, National Child Development Study (NCDS), Newcastle Thousand Families Cohort Study, Pelotas Birth Cohort Study (1993)).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these exposures, such as smoking (Garot et al, 2022), gestational hypertension (Fatturi et al, 2019), and TA B L E 2 Maternal characteristics and variables collected at birth (1997)(1998). cesarean delivery (Garot et al, 2022;Silva et al, 2016), have been associated with MIH (Alaluusua, 2010;Lopes et al, 2021) and can increase the risk of adverse pregnancy outcomes (Xie et al, 2022) which, in turn, will influence the babies health (Keag et al, 2018;Peres et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other variables related to the pregnant woman's health, such as a history of abortion, higher pre‐pregnancy BMI, smoking, gestational hypertension, and cesarean delivery, exhibited standardized coefficients of mild magnitude (>1), however, without statistical significance. Some of these exposures, such as smoking (Garot et al., 2022), gestational hypertension (Fatturi et al., 2019), and cesarean delivery (Garot et al., 2022; Silva et al., 2016), have been associated with MIH (Alaluusua, 2010; Lopes et al., 2021) and can increase the risk of adverse pregnancy outcomes (Xie et al., 2022) which, in turn, will influence the babies health (Keag et al., 2018; Peres et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies have measured oral health outcomes in the past. Recently, Peres et al [ 5 ] presented an overview of existing oral health–related birth cohort studies worldwide. Of the 120 existing oral health–related birth cohort studies, there are 48 prospective cohort studies.…”
Section: Introductionmentioning
confidence: 99%